Beyond Curiosity: The Role of Inquisitiveness in Managing Epistemic Uncertainty and Problem-Solving Difficulties among Pre-Service Elementary Teachers - Fida Rahmantika Hadi; Mulyadi Mulyadi (FKIP Universitas Lampung, 2026)
This study investigates the relationship between inquisitiveness and problem-solving difficulties among pre-service elementary school teachers when solving mathematical problems containing contradictory information. The aim is to identify how different levels of inquisitiveness influence cognitive, metacognitive, and affective difficulties and to provide a deeper explanation of how these difficulties emerge during the reasoning process. A qualitative descriptive case study was conducted with 33 fifth-semester students in the Elementary Teacher Education program at Universitas PGRI Madiun. Data were collected through problem-solving tests, think-aloud, and interviews. Students were categorized into high, medium, and low inquisitiveness groups based on a questionnaire. Data analysis was carried out through coding, reduction, and triangulation across instruments, followed by cross-case comparison to ensure the consistency of themes and strengthen the interpretation of findings. The results showed that inquisitiveness strongly influenced the types and intensity of difficulties. Students with low inquisitiveness often experienced cognitive difficulties, such as reliance on formulas without verification, and affective difficulties, such as nervousness and frustration, which led them to stop. Students with medium inquisitiveness tended to experience metacognitive difficulties, recognizing contradictions but failing to regulate or adjust their strategies. High-inquisitiveness students demonstrated persistence and attempts at verification, although occasional metacognitive challenges still appeared. The study also found that inquisitiveness shaped students’ emotional responses, with higher inquisitiveness associated with greater tolerance for confusion and a stronger willingness to re-evaluate conflicting information. Inquisitiveness plays a critical role in supporting conceptual verification, self-regulation, and emotional resilience when solving mathematical problems with contradictory information. These findings emphasize that inquisitiveness is not merely a cognitive trait but also an affective resource that helps students manage uncertainty. Strengthening this disposition may improve future teachers’ reasoning and their ability to guide students through complex problem-solving situations. Keywords: inquisitiveness, problem solving difficulties, contradictory information, pre-service elementary teachers.